Challenges Affecting the Effectiveness of Women Organizations in Community Development in Niger State - Lakan, M. J.; Lemu, H. I.; Abdullahi, S.; Umar, Y. (Journal of Research in Adult and Continuing Education, 2025)
This study investigates the challenges affecting the effectiveness of women organizations in driving community development initiatives across Niger State, Nigeria. Women organizations are vital stakeholders in grassroots mobilization, socio-economic empowerment, and civic participation, yet their contributions are often hindered by contextual limitations. The study adopted a mixed-methods approach, combining quantitative and qualitative techniques to provide a comprehensive understanding of the issues. The population comprised registered women organizations across Niger State, from which a sample of 360 participants was drawn using stratified and purposive sampling techniques to ensure representation across six local government areas within the three geopolitical zones. Data were collected using a structured questionnaire and in-depth interviews. The questionnaire items were validated by experts in community development and gender studies, while reliability was established through a pilot test that yielded a Cronbach’s alpha of 0.82. Quantitative data were analyzed using descriptive and inferential statistics such as frequency counts, percentages, and chi-square tests, while qualitative data were subjected to thematic analysis. The findings revealed that financial limitations, cultural and religious restrictions, weak leadership structures, and inadequate government support significantly reduce the operational effectiveness of these organizations. The study recommends policy reforms, sustainable funding mechanisms, and community-based sensitization to strengthen the capacity of women organizations in promoting inclusive development.
Keywords: Women organizations; community development; challenges; Niger State; grassroots participation